Five years experiences in diagnosis and management of jejuno-ileal atresia in Kanti children’s hospital - Basnet, Anupama; Thapa, Bijay; Dhoubadel, Prativa; Kayastha, Anuj (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Jejuno-ileal atresia is a major cause of neonatal intestinal obstruction. The aim of this study is to evaluate the incidence, clinical presentation, management, and outcome of jejunoileal atresia at our institute over a period of five years.Methods: The medical records of the patients with the diagnosis of jejunoileal atresia during a period of five years (April 2014 to April 2019) were obtained from the hospital record section and surgical intensive care unit, and were reviewed and analyzed.Results: There were 61 cases of jejunoileal atresia among 144 cases of intestinal atresia. Twenty-nine (47.5%) of them were male. Laparotomy with resection of atretic part with anti-mesenteric tapering enteroplasty and end to end anastomosis was done in 15, and resection without tapering enteroplasty with end to end anastomosis was done in 39 patients. Thirty-eight patients (62.3%) were discharged while Twenty-three (37.7%) cases were lost to mortality.Conclusions: Although the mortality and morbidity rate are high in jejunoileal atresia, early diagnosis, improvement in surgical technique, modern ventilatory support and advanced in intensive care unit has led to the significant increase in the survival rate.